Southeast Asian affairs 2016 - Cook, Malcolm, 1970-; Singh, Daljit (Singapore : Institue of Southeast Asian Studies, 2016)
'Southeast Asian Affairs, first published in 1974, continues today to be required reading for not only scholars but the general public interested in in-depth analysis of critical cultural, economic and political issues in Southeast Asia. In this annual review of the region, renowned academics provide comprehensive and stimulating commentary that furthers understanding of not only the region's dynamism but also of its tensions and conflicts. It is a must read.' - Suchit Bunbongkarn, Emeritus Professor, Chulalongkorn University. 'Now in its forty-third edition, Southeast Asian Affairs offers an indispensable guide to this fascinating region. Lively, analytical, authoritative, and accessible, there is nothing comparable in quality or range to this series. It is a must read for academics, government officials, the business community, the media, and anybody with an interest in contemporary Southeast Asia. Drawing on its unparalleled network of researchers and commentators, ISEAS is to be congratulated for producing this major contribution to our understanding of this diverse and fast-changing region, to a consistently high standard and in a timely manner.' - Hal Hill, H.W. Arndt Professor of Southeast Asian Economies, Australian National University
Foreword / Tan Chin Tiong -- Introduction / Vandana Prakash Nair and Malcolm Cook -- The region. Southeast Asia's regional autonomy under stress / Carlyle A. Thayer -- Southeast Asian economies coping with adverse global economic conditions / Cassey Lee -- U.S.-Southeast Asia relations in the age of the rebalance / William T. Tow -- China's international strategy and its implications for Southeast Asia / Zhang Zhexin -- Japan's'strategic coordination' in 2015 : ASEAN, Southeast Asia, and Abe's diplomatic agenda / Kei Koga -- India's act east policy and implications for Southeast Asia / Amitendu Palit -- Brunei Darussalam. Brunei Darussalam : challenging stability / Christopher B. Roberts and Malcolm Cook -- Cambodia. Cambodia in 2015 : accommodating generational change / Sophat Soeung -- Indonesia. Indonesia in 2015 / Robin Bush -- Indonesia's infrastructure development under the Jokowi administration / Siwage Dharma Negara -- Laos. Laos in 2015 : a pivotal year in moving towards the AEC / Buavanh Vilavong -- Malaysia. Malaysia in 2015 : crises of confidence / Prashanth Parameswaran -- Malaysia's higher education and quest for developed nation status by 2020 / Viswanathan Selvaratnam -- Myanmar. Myanmar in 2015 : hki'mala. dukka or hard times / Robert H. Taylor -- Myanmar's general election 2015 : change was the name of the game / Tin Maung Maung Than -- The Philippines. The Philippines in 2015 : slowly, on the straight and narrow / Maria Elissa Jayme Lao -- The sustainability of recent Philippine economic growth / Leonardo A. Lanzona, Jr. -- Singapore. Singapore in 2015 : SG50 -- Norman Vasu and Damien D. Cheong -- Thailand. Thailand in 2015 : the waiting game / Serhat Ünaldi -- Being Thai : a narrow identity in a wide world / Nicholas Farrelly -- Timor-Leste. Timor-Leste in 2015 : petro-politics or sustainable growth / Maj Nygaard-Christensen -- Vietnam. Vietnam in 2015 : challenges persist amidst hope for change / Le Hong Hiep -- Vietnam : in search of a new growth model / Jonathan Pincus.
Title from publisher's bibliographic system (viewed on 05 Jun 2017).
Keywords: Southeast Asia -- Economic conditions; Southeast Asia -- Politics and government; Southeast Asia -- Economic policy